Genetic Influence of Candidate Osteoporosis Genes in Saudi Arabian Population: A Pilot Study. (1st April 2012) - Sadat-Ali, Mir; Al-Turki, Haifa A.
Abstract : Background and Objectives . The purpose of the present study is to find the genes and SNP that influence BMD and postmenopausal Saudi women. Material and Methods . Two-hundred ethnic Saudi Arabian women with a diagnosis of postmenopausal osteoporosis were the subjects of this study. Baseline blood hematology, biochemistry, and bone panel were done. Blood was collected, and three TaqMan-MGB probes were used to analyze SNP variants in ALOX15 (rs7220870), LRP5 (C 25752205 10), and TNFRSF11B (C 11869235 10). Results . The variant of ALOX15 17p13 showed that the BMD of the spine was lower in the AA allele (P value< 0.002 ) and fractures were highest at 50% compared to CC allele. In the TNFRSF11B gene, BMD of the hip and spine was significantly higher in the GG allele and the history of fractures was significantly higher in GG group. With regard to the LRP5 (C 25752205 10) gene, there was no significant difference between allele groups. Conclusion(s) . This study shows that the genetic influence of osteoporosis in the Caucasian and Saudi Arabians population is similar. We believe that the same genetic markers that influence osteoporosis in the Caucasian race could be used for further studies in the Saudi Arabian population.